PENDIDIKAN TOLERANSI HIDUP BERAGAMA DI YAPIS PAPUA - Dute, Hasrudin (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
The purpose of this paper is to find out the religious life of students at the Yapis Jayapura educational institution. This writing method is descriptive qualitative, with data collection from several research results, books, observations and interviews about the Yapis Papua Islamic educational institutions. The results of this paper indicate that religious tolerance education has been applied in Yapis Papua educational institutions. Because the idea of religious tolerance is not difficult, because the teachings of each religion, especially Islam teaches about mutual recognition and respect for other parties, differences in terms of language, religious culture and even ethnicity can be accepted and must be accepted as sunnatullah, as good things that come it's from Allah.